Handbook of cathodic corrosion protection : theory and practice of electrochemical protection processes - Baeckmann, W. von (Walter); Schwenk, W. (Wilhelm); Prinz, W.; Baeckmann, W. von (Walter) (Gulf Pub. Co., 1997)
This comprehensive handbook covers all aspects of cathodic protection in terms of both practice and theory.